Pengaruh Ukuran Perusahaan, Profitabilitas, Struktur Modal, Leverage dan Kepemilikan Institusional Terhadap Nilai Perusahaan - Hersintha Sahara; Kartika Hendra Titisari; Purnama Siddi (Owner : Riset dan Jurnal Akuntansi, 2022)
This research aims to examine and analyze the effect of company size, profitability, capital structure, leverage & institutional ownership on firm value in property & real estate companies listed on the IDX (Indonesia Stock Exchange) from 2015-2019 period. The population obtained was 35 companies in research is property & real estate companies listed on the IDX (Indonesia Stock Exchange) from 2015-2019 period & the sample obtained was 20 companies. Sampling method used in research was “purposive sampling”. This type of research is quantitative research. The type of research used in in this research is descriptive quantitative. The research data source is secondary data obtained form the annual financial statements. The data analysis used is multiple linear regression, the coefficient of determinantion test, the classical assumption test, the F test & the hypothesis test. The results of the study showed that company size (SIZE), profitability (ROA), capital structure (DER) and leverage (DAR) affect on firm value (PBV) in property and real estate companies listed on the IDX (Indonesia Stock Exchange) from 2015-2019 period, while institutional ownership (INST) not affect on firm value (PBV) in property & real estate companies listed on the IDX (Indonesia Stock Exchange) for 2015-2019 period.